SUPPORTING AND INHIBITING FACTORS FOR DEVELOPING AKHLAKUL KARIMAH IN STUDENTS OF MADRASAH TSANAWIYAH STATE 1 MAKASSAR - Saharuddin, Saharuddin; Mahmud, Moch Natsir; Ondeng, Syarifuddin; Rahman, Ulfiani (Jurnal Diskursus Islam, 2019)
This paper will examine the supporting and inhibiting factors in the cultivation of moral behavior in students of Madrasah Tsanawiyah Negeri 1 Makassar City. This study is classified as a qualitative study with the location of the Madrasah Tsanawiyah state I Makassar study site. The approach used is a normative juridical approach, pedagogical approach, theological approach, psychological approach, phenomenological approach, ethnometodological approach, and symbolic interaction approach. Data processing and analysis is done by data reduction, data presentation, and drawing conclusions. The validity of the data of this study was carried out through the stage of checking the credibility of the data with persistent observational techniques and source triangulation. Research results show that supporting planting morality in MTs Negeri 1 Makassar through three channels, namely (1) planting morality in learning, (2) planting morality in the extracurricular activities, (3) Students are all Muslim. The main obstacle to the cultivation of morality in the MTs Negeri 1 Makassar is in the teaching of teachers in the classroom. More specifically, the obstacle experienced by teachers is the lack of exercise books, the unavailability of funds for activities outside the madrasah and the absence of specialist teachers in the field of morality cultivation in MTs Negeri 1 Makassar City. Furthermore, the inhibitors of planting morality in MTs Negeri 1 Makassar City are (a) the lack of facilities and infrastructure in the form of Islamic religious education laboratories slightly inhibits the seeding of moral values in students, (b) education is faced with Student diversity, the belief side in one religion, and (c) Students have different backgrounds in life.